Geomembrane Filter Thread Technique’s Potential to Increase Salt Production in Jeneponto Regency - Zakia Asrifah Ramly; Nur Ahmad; Nur Asriyanti Juhaseng (Indonesian Journal of Environmental Management and Sustainability, 2022)
The problem of salt production byJeneponto Regency is influenced by the traditional way of making salt. The introduction of GFTT (Geomembrane Filter Thread Technique) as a salt-making technology is an effort to increase salt production in the Jeneponto district, both in quality and quantity. This activity was carried out in Biring Parang Jaya Village, Jeneponto Regency. Activities are carried out by applying threaded techniques to salt ponds, making filter devices on salt ponds, and installing geomembranes as salt tablets. Based on the application of technology, the salt produced by GFTT has better quality and quantity than traditional salt. Salt produced by GFTT is classified as high grade with 99.96% NaCl and 0.04% moisture content.